Perancangan Aplikasi Metode Felics Untuk Kompresi Data Video Dengan Ekstensi AVI - Meiberiang Zebua (Graha Mitra Edukasi, 2023)
Technological developments at this time are inseparable from problems related to data storage which often limits the amount of capacity, especially in storing video data. In this case the author designed a video compression application to make video file dimensions with small dimensions which previously had a fairly large capacity are now smaller. The purpose of compression is to change data related to information whose capacity is large enough so that the data capacity becomes smaller and lighter in the transmission process. In addition to the problems above related to technological developments, it also often limits capacity when transmitting video files, therefore the authors designed an application for this FELICS method so that each limited capacity can produce capacity according to the specified needs. To overcome this problem, a compression application design was created so that video files can be reduced in capacity. By using the FELICS method, the process of designing Video data compression applications is easier to do. Based on the resulting compression ratio value, the compression value of the FELICS method is 60%. Meanwhile, the value of applying the FELICS method can be seen from the Space saving value of 0.4.